Benefits and challenges of BIBFRAME: Cataloging special format materials, implementation, and continuing educational resources. Issue 3 (16th September 2019) - Park, Jung-Ran; Richards, Lorraine L.; Brenza, Andrew
Abstract : Purpose: The purpose of this paper is to highlight the potential strengths and weaknesses of the BIBFRAME bibliographic model and outline its purpose and key features. In addition, it discusses specific aspects of the model with respect to the pre-existing models of bibliographic description. Design/methodology/approach: A review of source and secondary materials regarding BIBFRAME was undertaken, and a comparison of the conclusions derived from this literature was made to the pre-existing models of bibliographic description. Findings: If the BIBFRAME Initiative can overcome what will likely be some significant challenges to the development and implementation of the model, BIBFRAME appears to be poised to become the next standard of bibliographic description and exchange for the library community. Research limitations/implications: The findings and conclusions of this paper are based upon an in-depth literature review, not on theoretical or empirical derivations or examples. As a result, further research of both theoretical and empirical natures need to be developed. Practical implications: BIBFRAME may well become the next standard of bibliographic description and exchange for the library community, leading to significant changes in cataloging practices over the years. Social implications: To the extent that BIBFRAME can expand discovery mechanisms, the vast array of information currently available to information seekers will open up in previously unthought of ways. Originality/value: This paper synthesizes a literature that was developed during a more preliminary design of the bibliographic model BIBFRAME and adds to the literature by discussing newer capabilities that have been designed into BIBFRAME 2.0.